2016
DOI: 10.1055/s-0036-1592144
|View full text |Cite
|
Sign up to set email alerts
|

Distance between Great Vessels and the Lumbar Spine: MRI Study for Anterior Longitudinal Ligament Release Through a Lateral Approach

Abstract: Anterior column reconstruction using the lateral transpsoas approach requires sectioning of the anterior longitudinal ligament while protecting the great vessels. Our aim was to study the anatomical plane of separation between the retroperitoneal vessels and the anterior aspect of the lumbar spine as they relate to safety in the lateral transpsoas anterior column reconstruction procedure. A total of 100 T2-weighted magnetic resonance imaging (MRI) examinations were studied. Measurements were obtained for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The mean distance of arteries at the level of L4-L5 was 4.3 mm in the supine and prone position [39]. A study by Marchi et al [40] showed the areolar space to be narrow in the supine position, especially in the lower lumbar segment. The same study also indicated that the areolar space could be maximized in the lateral patient position, while the average values of areolar space in relation to inferior vena cava were larger in the superior lumbar segment.…”
Section: Discussionmentioning
confidence: 92%
“…The mean distance of arteries at the level of L4-L5 was 4.3 mm in the supine and prone position [39]. A study by Marchi et al [40] showed the areolar space to be narrow in the supine position, especially in the lower lumbar segment. The same study also indicated that the areolar space could be maximized in the lateral patient position, while the average values of areolar space in relation to inferior vena cava were larger in the superior lumbar segment.…”
Section: Discussionmentioning
confidence: 92%
“…The lateral decubitus position is generally used in spine surgery for transthoracic or thoracoabdominal lateral vertebral column access, although its usage in posterior cervical spine surgery is seldom reported. [4][5][6][7] In recent years, we have begun to use the lateral position in cervical laminoplasty in our hospital, we found that the lateral position has some advantages over the prone position. The lateral position facilitates surgical field drainage and intraspinal inspection (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 93%
“…Se registró también si la posición del psoas era demasiado anterior (signo de Mickey Mouse o the rising psoas). 16 Se utilizó el método Moro 17 que divide el espacio intervertebral en seis zonas que van de anterior a posterior (Figuras 1 y 2). El aspecto anterior del margen anterior del cuerpo vertebral fue definido como zona A; el aspecto posterior del margen posterior, como zona P; las zonas I, II, III, IV fueron distribuidas igualmente entre el margen anterior y el margen posterior, del anterior al posterior.…”
Section: Diseño Del Estudiounclassified
“…11 Sin embargo, la distribución de los vasos grandes abdominales y los músculos psoas principales de cada espacio intervertebral lumbar es inconsistente. [12][13][14][15] Hay pocas publicaciones que describen la anatomía usando imágenes por resonancia magnética (RM), 12,16 y la muestra es pequeña.…”
Section: Introductionunclassified